Peningkatan Profesionalisme Guru Melalui Pelatihan Penulisan Karya Ilmiah bagi Kepala Sekolah dan Guru di Pulau Untung Jawa - Silvie, Silvie; Ekawati, Anita Dewi; Ningsih, Sri Kusuma (Universitas Pahlawan Tuanku Tambusai, 2025)
Writing scientific papers can train thinking skills, become a vehicle for practicing ideas and ideas as well as a medium for knowledge transformation. This community service activity aims to improve the ability of school principals and teachers on the Untung Jawa island to produce scientific publications. The training was conducted by organizing seminars and workshops for all levels of education on the island. This activity was attended by thirty people consisting of Principals and teachers of PAUD, TK, PKBM and SMP on the Untung Jawa Island, Kepulauan Seribu. At the seminar, participants listened to material about the theory and concept of scientific papers by keynote speaker. In the workshop activities, each participant made scientific papers. The result of this service activity is that all participants can make scientific papers based on their respective ideas that can be published in accredited national journals and included in scientific writing competitions. Writing scientific papers can help principals and teachers improve their professionalism and creativity. It is hoped that with this training, educators can publish their ideas in accredited scientific journals and participate in scientific writing competitions.